Racial invariance in rural and urban contexts: comparing the structural sources of Black, White, and Latinx homicide in rural and urban counties, 2000 and 2010 - Allen, Caroline B. (Journal of ethnicity in criminal justice, 2022)
Structural disadvantage has long been empirically linked to violent crime across different race/ethnic groups. More recently conceptualized as “racial invariance,” observed racial differences in crime rates are hypothesized to be the result of disparities in community-level structural conditions. However, most investigations into this hypothesis have focused on urban settings, with limited attention to rural contexts. The current study seeks to fill this gap by comparing county-level structural predictors of homicide victimization for Black, White, and Latinx populations in both urban and rural communities. Consistent with the racial invariance hypothesis, findings reveal that disadvantage strongly predicts homicide across race/ethnicity in both rural and urban counties. Closer inspection of results, however, exposes noteworthy differences in the effects in rural and urban settings.